The PROSES PRODUKSI LAGU DIVERT DALAM INDUSTRI MUSIK INDIE KARYA FALLEN ROSE BAND LOKAL ASAL SURABAYA - Rachell Sevilya Putri; senyum sadhana (Universitas Negeri Surabaya, 2026)
Fallen Rose is a local band from Surabaya with an alternative rock subgenre and stands independently without being under the auspices of a record label. One of the works produced by the band is the song